Structural and electronic properties of orthorhombic phase Bi₂Se₃ based on first-principles study / Muhammad Zamir Mohyedin ... [et al.] - Mohyedin, Muhammad Zamir; Radzwan, Afiq; Mohamad Taib, Mohammad Fariz; Zakaria, Rosnah; Jaafar, Nor Kartini; Mustaffa, Masnawi; Ahmad Aini, Nazli (Penerbit UiTM (UiTM Press), 2019)
Bi₂Se₃ is one of the promising materials in thermoelectric devices and is environmentally friendly due to its efficiency to perform in room temperature. Structural and electronic properties of Bi2Se3 were investigated based on the first-principles calculation of density functional theory (DFT) using CASTEP computer code. The calculation is conducted within the exchange-correlation of local density approximation (LDA) and generalised gradient approximation within the revision of Perdew-Burke-Ernzerhof (GGA-PBE) functional. A comparative study is carried out between the electronic properties of LDA and GGA-PBE. Lattice parameter and band gap are consistent with the other reports. Calculation from LDA is more accurate and has a better agreement than GGA-PBE in describing the lattice parameter of Bi2Se3. Band gap and density of states of LDA show higher electrical conductivity than GGA-PBE. Both LDA and GGA-PBE have same degree of thermal conductivity due to the occurrence of indirect band gap at same range of wave vector.